Bidirectional loop-snare technique for adherent inferior vena cava filter retrieval - Akazawa, Ryota; Ishibashi, Naoki; Fujiwara, Takashi; Watanabe, Yoshikazu; Shokawa, Tomoki; Maeda, Koji; Tsujiyama, Shuji; Fujii, Takashi (Journal of cardiology cases, 2019)
Placement of a Günther Tulip Inferior Vena Cava (IVC) Filter™ (Cook, Bloomington, IN, USA) is an alternative treatment option to prevent pulmonary embolism in patients in whom anticoagulation therapy is contraindicated. Most patients require filter placement for only short periods, after which it can be retrieved. IVC filter retrieval becomes more difficult as the indwelling time increases. We developed a new method to retrieve the Günther Tulip IVC Filter™, namely, the bidirectional loop-snare technique (BLT). The key to the BLT procedure is to use 2 snares from both the jugular and femoral access routes. The jugular snare catches the filter hook and the femoral snare relieves the adhesion between the filter leg and IVC wall. Pulling from both the jugular and femoral ends increases the power to retrieve the IVC filter, and leads to successful filter retrieval. <Learning objective: An inferior vena cava (IVC) filter is placed in patients with a risk of pulmonary embolism. Most patients require filter placement for only short periods, after which it can be retrieved. Occasionally, IVC filter retrieval is difficult because of long-term placement. We developed a novel, simple method for filter retrieval, using a bidirectional approach and two snares simultaneously.>